Being in a hospital room alone with the diagnosis of Covid-19 from a patient perspective: a qualitative study - (:unkn) unknown (CUKUROVA UNIV, FAC MEDICINE, 2021)
Purpose: The aim of this study was to investigate common themes for psychological interventions and support in patients hospitalized with the diagnosis of Covid-19 and to examine the psychosocial impacts of isolation from the patient perspective during early phase of Coronavirus pandemic in a tertiary center in Istanbul. Materals and Methods: The data were collected from phone calls and hospital records of hospitalized patients suspected or diagnosed with Covid-19 during the second half of March 2020. In the content analysis of qualitative data, codes, categories and themes were extracted from the events and phenomena frequently repeated or emphasized by the participants. Results: A total of 38 people, 18 women and 20 men, were included in the study. Four general themes were established: unexpected illness, isolation, uncertainty, stigmatization. First, it was observed that the unexpected emergence of the disease induced a shock response, the defense of denial was on duty, and the interruption of life plans could not be accepted. The perceptions of the patients under being imprisoned theme were being punished, feeling of regret, the thoughts of opposing authority, running away, harming themselves or others. Conclusion: Focusing on the psychological aspects of isolation is effective not only in reducing stress, anxiety, depression in the long term, but also increases motivation and compliance with quarantine practices and rules at the very beginning.
Keywords: Coronavirus; quarantine; loneliness; social support; pandemic; acting out; EXPERIENCE; TUBERCULOSIS; SARS-COV-2; DEPRESSION; QUARANTINE; EPIDEMIC; STIGMA; CARE